The effects of aqueous ginger extract on aluminium chloride (AlCl3) induced alteration in lipid profile of male wister rats - Dass, Asha P.; Ramoji, Prashanth Chary (International Journal of Basic & Clinical Pharmacology, 2017)
Background: This study was aimed at investigating the effects of aluminium chloride (AlCl3) in altering the serum lipid profiles and ways to reduce its effect using two different doses of ginger extract 500mg/kg and 1000mg/kg body weight in male wister rats. Methods: The rats were randomly divided into 4 groups consisting of 5 animals in each group. Groups II, III and IV received AlCl3 100mg/kg bodyweight single dose, Groups III and IV receiving an additional daily oral single dose of ginger plant extract through a stomach tube. All animals were fasted before the treatment. All rats were weighed before the start of the experiment and at the end of the experiment. The blood was collected firstly at the beginning of the experiment, then on the 45th day. The collected blood was left to clot then centrifuged at 3500 rpm for 5 min. The serum was separated and stored at - 80°C for later analyses. Results: This study shows that a single dose of 100mg/kg aluminium chloride causes a rise in total body weight, TC (total cholesterol), LDL (low density lipoproteins) and TG (triglycerides) levels in the rat, and aqueous Zingiber officinal (ginger) extract reduces this rise in TC, LDL and TG levels in the rats. Conclusions: Ginger was effective in lowering serum cholesterol levels levels in the ginger treated rats to almost normal value. These results indicate that treatment with aqueous extract of ginger may be effective in lowering lipid levels in AlCl3 induced hyperlipidemia in rats.